Plasmodium merozoite TRAP family protein Is essential for vacuole membrane disruption and gamete egress from erythrocytes - Bargieri,DY; Thiberge,S; Tay,CL; Carey,AF; Rantz,A; Hischen,F; Lorthiois,A; Straschil,U; Singh,P; Singh,S; Triglia,T; Tsuboi,T; et al. (Cell Host & Microbe, 2016)
Surface-associated TRAP (thrombospondin-related anonymous protein) family proteins are conserved across the phylum of apicomplexan parasites. TRAP proteins are thought to play an integral role in parasite motility and cell invasion by linking the extracellular environment with the parasite submembrane actomyosin motor. Blood stage forms of the malaria parasite Plasmodium express a TRAP family protein called merozoite-TRAP (MTRAP) that has been implicated in erythrocyte invasion. Using MTRAP-deficient mutants of the rodent-infecting P. berghei and human-infecting P. falciparum parasites, we show that MTRAP is dispensable for erythrocyte invasion. Instead, MTRAP is essential for gamete egress from erythrocytes, where it is necessary for the disruption of the gamete-containing parasitophorous vacuole membrane, and thus for parasite transmission to mosquitoes. This indicates that motor-binding TRAP family members function not just in parasite motility and cell invasion but also in membrane disruption and cell egress.